2007
DOI: 10.1111/j.1467-9248.2007.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Winning, Losing and Satisfaction with Democracy

Abstract: Previous research has shown that those who won an election are more satisfied with the way democracy works than those who lost. What is not clear, however, is whether it is the fact of winning (losing), per se, that generates (dis)satisfaction with democracy. The current study explores this winner/loser gap with the use of the 1997 Canadian federal election panel study. It makes a theoretical and methodological contribution to our understanding of the factors that foster satisfaction with democracy. At the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
224
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(231 citation statements)
references
References 34 publications
3
224
0
4
Order By: Relevance
“…Before delving into the results of the multilevel models, we first present straightforward macro-level evidence on the general relationship between sociotropic congruence and 12 Anderson et al, 2005;Anderson and Guillory, 1997;Anderson and Tverdova, 2001;Anderson and LoTempio, 2002;Anderson and Mendes, 2006;Banducci and Karp, 2003;Blais and Gélineau, 2007;Curini et al 2012;Moehler, 2009;Singh 2013;Singh et al 2012. 13 Descriptive statistics for the variables included in our analyses can be found in the appendix, Table A2.…”
Section: Resultsmentioning
confidence: 99%
“…Before delving into the results of the multilevel models, we first present straightforward macro-level evidence on the general relationship between sociotropic congruence and 12 Anderson et al, 2005;Anderson and Guillory, 1997;Anderson and Tverdova, 2001;Anderson and LoTempio, 2002;Anderson and Mendes, 2006;Banducci and Karp, 2003;Blais and Gélineau, 2007;Curini et al 2012;Moehler, 2009;Singh 2013;Singh et al 2012. 13 Descriptive statistics for the variables included in our analyses can be found in the appendix, Table A2.…”
Section: Resultsmentioning
confidence: 99%
“…Increases in satisfaction with democracy were observed in the 1999 legislative election in New Zealand (Banducci and Karp 2003), the 2010 North RhineWestphalia election (Singh, Karakoç, and Blais 2012), and the French presidential election of 2012 (Beaudonnet et al 2014). Blais and Gélineau (2007) found a positive effect on voters in general and winners, particularly in the Canadian election of 1997. Finally, Blais, Morin-Chassé, and Singh (2015) found that satisfaction increased among those who voted for parties that gained greater shares of votes, seats, and cabinet portfolios.…”
Section: Hypothesis 5: Satisfaction With Democracy Increases the Mostmentioning
confidence: 99%
“…Does it measure overall democratic performance, trust in specific institutions, trust in politicians, support for democratic principles, or some mixture of these (Canache, Mondak, and Seligson 2001;Linde and Ekman 2003)? Its defenders agree that the meaning is unclear but maintain its usefulness as an overall measure of subjective legitimacy and trust (Klingemann 1999;Anderson 2002;Blais and Gélineau 2007). Given our interest in broad generalizations from specific events, our position is that multiple measures and finer distinctions would be desirable but are not absolutely crucial as long as we capture much of the broad category of general political trust.…”
Section: Measurement and Datamentioning
confidence: 99%